Recensioni - Daniela Mario; Daniele Morselli; Giuseppe Longo; Francesca Lazzari; Francesco Caviglia; Irith Davidzon (Pensa MultiMedia, 2015)
Massimo Piattelli Palmarini, Le scienze cognitive classiche: un panorama di Daniela Mario Arthur L. Costa, Bena Kallick, Habits of Mind: A developmental series, Association Supervision for Curriculum Development di Daniele Morselli Sarah-Jayne Blakemore, Uta Frith, The Learning Brain: Lessons for Education di Giuseppe Longo Xenia Chryssochoou, Cultural diversity. Its social psychology di Francesca Lazzari Carl Bereiter, Education and mind in the knowledge age di Francesco Caviglia Isabel Beck, Margareth McKeown, Improving Comprehension with Questioning the Author: A Fresh and Expanded View of a Powerful Approach di Irith Davidzon